Antibacterial activity of vernonia cinerea, peperomia pellucida and combination of vernonia cinerea and peperomia pellucida / Noor Zarifah Zamri - Zamri, Noor Zarifah (2018)
The present of research was conducted to determine the antibacterial activity of Vernonia cinerea, Peperomia pellucida of combination of the Vernonia cinerea and Peperomia pellucida. The extracts were assayed for antibacterial against Staphylococcus aureus and Escherichia coli by using disc diffusion method. Gentamycin was used as the positive control. The result showed that combination of the Vernonia cinerea and Peperomia pellucida have potential to become new antibacterial agents as it inhibit 11mm growth of Escherichia coli at 50mg/ml. The minimum inhibition concentration also showed the lowest concentration of inhibit the growth in Escherichia coli is 100mg/ml while for Staphylococcus aureus is 50 mg/ml by using extraction of combination of Vernonia cinerea and Peperomia pellucida.